Improving Students’ Speaking Ability by Using Movie Media in Grade 9 Junior High School 4 Pematangsiantar - Saragih, Natanael; Saragih, Amrin (EXCELLENCE: Journal of English and English Education, 2024)
Students are expected to speak and communicate in English in daily life, both in the written and spoken form. Many teachers are not really aware of the problems in teaching speaking. The purpose of this research was to determine using short animation movie as media to improve students’ speaking ability. Data was collected by giving pre-test and post-test. The population of this research was 309 people and the research sample was students of class IX SMPN 4 Pematangsiantar year 2023/2024. The researcher took 1 sample was of class IX-10 SMPN 4 Pematangsiantar which consisted of 30 students. The sample was taken using purposive sampling technique. The result showed that the students ability to speaking English using Short Animation movie as media on the pre-test and post-test differend significantly. The post-test has a higher score that the pre-test. That is F counted =1031,2> F table = 3,98. The researcher got that data analysis hypothesis test above the significance value =0.00 (p<0.05). So,that hypothesis (H0) is rejected and hypothesis (H1) automatically accepted. This indicated that students gave very positive responses or agreed that using short animation movie could motivate and interest the students in speak English much better. Therefore, movie is considered as an effective media in learning English. It was also expected that the teacher using short animation movie students to speak and the teachers should be creative or give instruction in using teaching media to make learning more effective